Representation of Justice in the Phenomenon of No Viral No Justice and the Shadow of the Electronic Information and Transaction Law - Muhamad Iqbal; Iin Indriani; Susanto (Faculty of Law, Universitas Pekalongan, 2025)
The concept of viral has become a new phenomenon in society, which is different from oral rumors or traditional issues because it manifests itself in the form of content on social media. Although it is considered a channel for free speech, virality is often based on emotion and subjectivity, thus giving rise to debates regarding the justice it produces. The phenomenon of